They are 33 and 65
Equation: y-3 = -5(x-6) => y = -5x+33
Equation: y-3 = -5(x-6) => y = -5x+33
If you mean a slope of -5 and a point of (6, 3) then the equation is y = -5x+33
X = 5 or -5 3x2 - 42 = 33 3x2 = 75 x2=25
3q + 5 + 2q + 5 = 65 5q + 10 = 65 5q = 55 q = 11 Check it. 33 + 5 + 22 + 5 = 65 It checks.
65
Slope: -5 Points: (6, 3) Equation: y = -5x+33
They are 33 and 65
Slope: -5 Points: (6, 3) Equation: y = -5x+33
Equation: y-3 = -5(x-6) => y = -5x+33
Equation: y-3 = -5(x-6) => y = -5x+33
If you mean a slope of -5 and a point of (6, 3) then the equation is y = -5x+33
Equation: y-3 = -5(x-6) => y = -5x+33
Equation: y-3 = -5(x-6) => y = -5x+33
X = 5 or -5 3x2 - 42 = 33 3x2 = 75 x2=25
13/3 = 65/15 11/5 = 33/15 65/15 - 33/15 = 32/15 or 2 and 2/15